2012
DOI: 10.1177/0022146512446832
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Resources and Management of Hypertension

Abstract: Hypertension is one of the most prevalent chronic diseases among older adults, but rates of blood pressure control are low. In this paper, we explore the role of social network ties and network-based resources (e.g., information and support) in hypertension diagnosis and management. We use data from the National Social Life, Health, and Aging Project (NSHAP) to identify older adults with undiagnosed or uncontrolled hypertension. We find that network characteristics and emotional support are associated with hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 83 publications
3
93
4
Order By: Relevance
“…Berkman and Syme's 1979 pioneering study of Alameda County, California, showed that individuals with no ties to others face higher mortality risk than 5 individuals with many contacts. Researchers have since extended this result to a broad range of health outcomes including people's capacity to cope with stress (Thoits 1995), hypertension (Cornwell and Waite 2012) and suicide attempts (Mueller and Abrutyn 2015). Networks offer the comfort of companionship, channel informational and emotional support, and provide access to resources and material goods (Berkman et al 2000, Wellman andFrank 2001).…”
Section: Theory and Evidencementioning
confidence: 99%
“…Berkman and Syme's 1979 pioneering study of Alameda County, California, showed that individuals with no ties to others face higher mortality risk than 5 individuals with many contacts. Researchers have since extended this result to a broad range of health outcomes including people's capacity to cope with stress (Thoits 1995), hypertension (Cornwell and Waite 2012) and suicide attempts (Mueller and Abrutyn 2015). Networks offer the comfort of companionship, channel informational and emotional support, and provide access to resources and material goods (Berkman et al 2000, Wellman andFrank 2001).…”
Section: Theory and Evidencementioning
confidence: 99%
“…Actual communication about health issues, however, may be a critical mechanism that facilitates social support and that is differentially distributed across various role relationships. In a recent study on how social ties help older adults manage chronic illness, Cornwell and Waite (2012) report that network membersdboth kin and non-kindprotect against undiagnosed and uncontrolled hypertension to the extent that they are likely to be consulted about matters of health. This finding fits the assumption that talking about health is an important dimension of the relationshipdi.e., a form of functional specificitydthat has health consequences above and beyond the mere presence of a tie (Perry & Pescosolido, 2010).…”
Section: Health Care and Network Ties: Conventional Carementioning
confidence: 99%
“…Adherence is significantly and positively correlated with patients' beliefs in the severity of the disease to be prevented or treated (i.e., disease threat [10]). Since hypertension is commonly asymptomatic, hypertensive patients are unlikely to follow the treatment because of discomfort or declining functioning [11].…”
Section: Introductionmentioning
confidence: 99%